Association of IGF‐1 and IGFBP‐3 levels with gastric cancer: A systematic review and meta‐analysis. Issue 11 (14th September 2021) - Liu, Hongyu; Gu, Huxia; Kutbi, Emad H.; Tan, Shing Cheng; Low, Teck Yew; Zhang, Chong
Abstract: Purpose: Many studies have investigated the association between serum IGF‐1 and IGFBP levels with gastric cancer (GC), but the results remained inconclusive. In this work, we performed a systematic review and meta‐analysis to examine the precise association of serum levels of IGF‐1 and IGFBP with GC. Methods: A comprehensive systematic search was carried out in PubMed/MEDLINE, SCOPUS, Web of Science, and EMBASE databases for (nested) case‐control studies that reported the levels of IGF‐1 and IGFBP in GC cases and healthy controls, from inception until October 2020. Weighted mean difference (WMD) was calculated for estimating combined effect size. Subgroup analysis was performed to identify the source of heterogeneity among studies. Results: We found eight and five eligible studies (with 1541 participants) which provided data for IGF‐1 and IGFBP, respectively. All studies on IGFBP reported the IGFBP‐3 isoform. The pooled results indicate that GC patients had significantly lower serum IGF‐1 [WMD = −26.21 ng/mL (95% CI, −45.58 to −6.85; P  = .008)] and IGFBP‐3 [WMD = −0.41 ng/mL (95% CI, −0.80 to −0.01; P  = .04; I 2  = 89.9%; P  < .001)] levels than those in healthy subjects. Significant heterogeneity was observed in the association, which could be attributed to the sample size of the studies. Conclusions: In conclusion, our study reveals a significantly lower level of IGF‐1 and IGFBP‐3 in GC patients compared with healthy control subjects.